Global Series and Stages for the Ordovician System: A Progress Report - S. FINNEY (Geologica Acta, 2005)
There is no global standard set of chronostratigraphic/geochronologic subdivisions for the Ordovician System/Period. British series/epochs are often used as de facto nomenclature on stratigraphic correlation charts and geologic time scales. However, they were not widely adopted outside of the British Isles because the high degree of biogeographic provincialism and ecologic differentiation of Ordovician faunas prevent the British series from being correlated with precision and high resolution. As a result, several independent and very different regional sets of series and constituent stages were established for the Ordovician System with each generally applicable to a different paleoplate or modern continent. Of course, this has greatly confused Ordovician chronostratigraphy/geochronology and often results in imprecise correlations of Ordovician stratigraphic successions. An example is the Argentine Precordillera where British series are traditionally used to correlate Ordovician strata that contain faunas of predominately Laurentian affinity. The Subcommission on Ordovician Stratigraphy of the International Commission on Stratigraphy is addressing this problem by developing a standard set of Global Series and Stages for the Ordovician System. The Subcommission has made considerable progress, but it must complete its work expeditiously. The new global standard will facilitate reliable global correlation. It will provide a common language for discussing Ordovician strata, fossils, and geologic events. It will be of fundamental importance in advancing research on Ordovician rocks worldwide.